2007
DOI: 10.1038/sj.leu.2404860
|View full text |Cite
|
Sign up to set email alerts
|

The histone deacetylase inhibitor ITF2357 has anti-leukemic activity in vitro and in vivo and inhibits IL-6 and VEGF production by stromal cells

Abstract: We have investigated the activity of ITF2357, a novel hydroxamate histone deacetylase inhibitor, on multiple myeloma (MM) and acute myelogenous leukemia (AML) cells in vitro and in vivo. ITF2357 induced apoptosis in 8/9 MM and 6/7 AML cell lines, as well as 4/4 MM and 18/20 AML freshly isolated cases, with a mean IC 50 of 0.2 lM. ITF2357 activated the intrinsic apoptotic pathway, upregulated p21 and downmodulated Bcl-2 and Mcl-1. The drug induced hyperacetylation of histone H3, H4 and tubulin. When studied in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
78
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(83 citation statements)
references
References 45 publications
5
78
0
Order By: Relevance
“…The GF-D8 cell line was the most resistant, in agreement with our previously published data. 19 We conclude that the HEL cells that carry the JAK2 V617F mutation are sensitive to at least 100-fold lower ITF2357 concentrations in colony assays, compared to CML and AML cell lines bearing wild-type JAK2. Although less dramatically, HEL cells are also more sensitive to ITF2357 in cytotoxicity assays.…”
Section: Resultsmentioning
confidence: 71%
See 2 more Smart Citations
“…The GF-D8 cell line was the most resistant, in agreement with our previously published data. 19 We conclude that the HEL cells that carry the JAK2 V617F mutation are sensitive to at least 100-fold lower ITF2357 concentrations in colony assays, compared to CML and AML cell lines bearing wild-type JAK2. Although less dramatically, HEL cells are also more sensitive to ITF2357 in cytotoxicity assays.…”
Section: Resultsmentioning
confidence: 71%
“…19 We therefore analyzed the cytotoxic effect of ITF2357 on the HEL and other cell lines in liquid culture. As shown in Figure 1b, ITF2357 was cytotoxic for all cell lines analyzed, but HEL cells were most sensitive, with an IC 50 of B0.1 mM compared to the other cell lines showing an IC 50 ranging from 0.25 to 41 mM (Po0.0001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As some HDAC inhibitors have the ability to reduce VEGF production, one of the most prominent angiogenic factors in MM, it is possible that JNJ-26481585 not only reduces the MVD through the inhibition of the tumor burden, but also by reducing the VEGF secretion from the MM cells as well as the stromal cells. 43,55,[62][63][64][65] On the other hand, JNJ-26481585 might also affect MVD directly as several HDAC inhibitors, such as valproic acid, trichostatin, NVP-LAQ824 and LBH589, have shown anti-angiogenic properties in vitro and in vivo by affecting endothelial cell survival and function directly. Several in vitro assays showed that HDACi inhibit endothelial cell proliferation, induce cell cycle arrest and inhibit endothelial cell function by decreasing endothelial cell migration, invasion and tube formation.…”
Section: Discussionmentioning
confidence: 99%
“…One class of HDACIs is the hydroxamate derivatives family of compounds whose prototype is suberoyl anilide hydroxamic acid (SAHA) [5], which is being tested clinically in several hematological malignancies and has obtained FDA approval for the treatment of cutaneous T-cell lymphoma [6][7][8][9][10][11][12][13][14][15]. Our group has recently reported that ITF2357, an orally effective member of the family of hydroxamate-derived HDACIs, is a potent inducer of apoptosis and death of MM cells in vitro [16]. In fact, eight of nine MM cell lines and freshly isolated BM samples from four MM patients underwent significant apoptosis when exposed to ITF2357 with a mean IC50 of about 0.17 μM.…”
Section: Introductionmentioning
confidence: 99%